2013
DOI: 10.4000/assr.25037
|View full text |Cite
|
Sign up to set email alerts
|

Businessmen, Priests and Parishes

Abstract: Beginning in the late socialist years, the religious situation changed massively and local authors describe this phenomenon as religious renaissance (renessans) or religious rebirth (vozrozhdenie) (E. Arinin, 2005a, 2005b; V. N. Konstantinov, 2003; L. A. Fevraleva, 2005). The widespread romantic picture of a religion that survived in remote places, however, is misleading because the recent revival of Orthodoxy largely depends on religious and political centers like Sergiev Posad, Vladimir or Moscow (M. Benovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Surveys conducted in the immediate aftermath of the collapse of the Soviet Union reported that 37% of the population in Russia, 39% in Ukraine, and 59% in Bulgaria 'describe themselves as Orthodox Christians' (Pew Research Center, 2017). Qualitative appreciations are difficult, yet characteristics include 'the forceful separation of religious life from the larger society' (Agadjanian & Roudometof, 2005: 12, emphasis in text), the formatting of religion into well-discernible and controllable institutions, as well as its privatisation and spiritualisation (Köllner, 2013). Depending on the country, Orthodoxy was either politicised (in favour of the regime, never in opposition as Catholicism in Poland), i.e.…”
Section: The Communist Experience: Radicalized Statisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys conducted in the immediate aftermath of the collapse of the Soviet Union reported that 37% of the population in Russia, 39% in Ukraine, and 59% in Bulgaria 'describe themselves as Orthodox Christians' (Pew Research Center, 2017). Qualitative appreciations are difficult, yet characteristics include 'the forceful separation of religious life from the larger society' (Agadjanian & Roudometof, 2005: 12, emphasis in text), the formatting of religion into well-discernible and controllable institutions, as well as its privatisation and spiritualisation (Köllner, 2013). Depending on the country, Orthodoxy was either politicised (in favour of the regime, never in opposition as Catholicism in Poland), i.e.…”
Section: The Communist Experience: Radicalized Statisationmentioning
confidence: 99%
“…In comparison, anthropologists (e.g. Köllner, 2012Köllner, , 2013Caldwell, 2005) have more readily remarked the coincidence of the shift to market economics and the religious revival, and used this in their analysis. Why is it then that sociologists have been blind to what is obvious for other disciplines?…”
mentioning
confidence: 99%
“…This finding can also be found in other states such as post-Soviet Russia where the career prospects for politicians and businesspeople increase when they declare their commitment to mainstream religions such as Orthodoxy in public. Religion, then, becomes a crucial marker showing the trustfulness of politicians, government officials or businesspeople although their actual relation to religion as such is much more complicated and rests on very different associations that include religious belief, religious practice or notions of belonging to the religious community (Koellner 2013(Koellner , 2020.…”
Section: Overview Of the Volumementioning
confidence: 99%